Hábitos alimentarios del mapachín (Procyon lotor) (Carnivora: Procyonidae) en un bosque muy húmedo tropical costero de Costa Rica - Carrillo, Eduardo; Wong, Grace; Rodríguez, Miguel A (Revista de Biología Tropical, 2001)
Raccoon (Procyon lotor) food habits were studied at Manuel Antonio National Park, a tropical rain forest in the Pacific coast of Costa Rica from May to December 1987, from September to December 1989 and from January to April 1990. A 134 feces sample size was used to assess the most important items in raccoon diet: two crab species (Gecarcinus quadratus and Cardisoma crassum) with a relative frequency of 0.94 in the rainy season of 1987, 0.76 in the rainy season of 1989 and 0.65 in the dry season of 1990. Fruits were the second category in importance, with relative frequencies of 0.09 for 1987, 0.32 for 1989 and 0.44 for 1990.